The Development of Test Instrument on The Excretion System to Measure Creative Thinking Skills - Maghfiroh, Ummu; Nulhakim, Lukman; Suryani, Dwi Indah (Jurnal Pendidikan MIPA, 2021)
The creative thinking ability test instrument is a form tool to measure student creative thinking skills. This study aims to develop a creative thinking ability test instrument and determine is validity level. The research method used in developing the test instrument is the Borg and Gall development method (1983). The research instrument used in this study was a validation sheet. The results of this study indicate that the research and development process carried out by the researchers is a potential problem, data collection, planning, product design development, design validation, and design revision. The validity level of the creative thinking ability test instrument on the concept of the human excretion system that the researcher developed was in the valid category with a value of 76.94%. The test instrument for the ability to think creatively on the concept of the human excretion system is valid for use in student trials. Keywords: Test instrument, creative thinking, excretion system DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp10-23